ANALISIS INVENTARISASI SAINS DI KECAMATAN LAMBITU SEBAGAI MEDIA PEMBELAJARAN DI SDN TETA - Emi haryani; Nurwalidainismawati; Yeni wardatunnissa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
science learning in elementary schools still faces limitations in learning media, while environmental and local cultural potentials have not been systematically inventoried. this condition leads to a lack of comprehensive data regarding the utilization of local potentials as science learning resources, especially at sdn teta. the purpose of this study is to analyze the scientific inventory of local potentials in lambitu district. this research uses a qualitative method with an exploratory approach. the research subjects consisted of 15 informants, including 6 teachers, 1 principal, 6 students, and 2 community leaders located in teta village, lambitu district. data were collected through observation, interviews, and documentation. data validity was ensured through source triangulation and technique triangulation. data analysis used the miles & huberman model through four stages, namely data collection, data reduction, data presentation, and conclusion drawing. the results showed that the daily habits of the teta village community in lambitu district are related to several topics in elementary school science learning. the usefulness of candlenut, guava leaves, betel leaves, ginger, java chili, katuk leaves, mahogany seeds, castor plants, and turmeric can serve as a science inventory in elementary school science learning in a contextual, applicable, and curriculum merdeka-aligned manner.